Guidelines for Developing Elderly’s Quality of Life in the Area of Khao Kaew Subdistrict Administrative Organization Lan Saka District, Nakhon Si Thammarat Province - Naknun, Patcharee; Piemmetta, Jakkapong; Sarunburana, Thanapon (Rajapark Journal, 2024)
The objectives of this research were 1) to study the quality of life; 2) to compare the quality of life classified according to personal characteristics; and 3) to develop guidelines for the quality of life. It is a mixed method with quantitative and qualitative research. The study population is elderly people aged 60 years and over with Thai nationality and domicile in the Khao Kaeo Subdistrict Administrative Organization, Lan Saka District, Nakhon Si Thammarat Province. The sample size was 290 people. The research tools were a questionnaire with a confidence value of.824 and an interview form. The research uses descriptive statistics and inferential statistics for testing hypotheses, namely T-test and one-way ANOVA, and content analysis techniques for analyzing qualitative data. The research results were as follows: 1) The quality of life of the elderly was at a high level overall. 2) The comparison of the quality of life of the elderly in the area of ​​Khao Kaeo Subdistrict Administrative Organization, Lan Saka District, Nakhon Si Thammarat Province, classified by personal factors overall, was statistically significantly different at level 05, except for the age factor. Furthermore, 3) development guidelines for the quality of life for the elderly in the area of ​​Khao Kaeo Subdistrict Administrative Organization, Lan Saka District, Nakhon Si Thammarat Province might promote the participation of all sectors in the quality of life in terms of physical, mental, and environmental aspects of social relations to enable the elderly to have a good quality of life.